The Social Piety of Female Itinerant Traders in Traditional Markets - Hanani, Silfia; Nelmaya, Nelmaya; Aldian, Elsa; Ulya, Zakiyah; Rahmana, Sitto; Limilia, Putri; Bt. Abdul Manaf, Azima; Sabastian, Aleena (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study examines changes in the social piety of female itinerant traders in traditional markets in the Minangkabau matrilineal cultural context in West Sumatra. Village religious traditions, common among non-mobilized women working as farmers, are compared with market religious traditions, which emerge among women working as itinerant traders. The change from the agricultural sector to the market sector influenced women's religious practices, from traditions characterized by mechanical rural norms to an organic and materialistic market orientation. This study uses holistic observation methods in two traditional markets and in-depth interviews with female itinerant traders. Findings suggest that the economic mobility of itinerant women traders creates different dynamics of social piety, with heterogeneous market interactions influencing their understanding and practice of religion. The piety formed reflects social solidarity and adaptation to changing economic conditions, with primary indicators including helping, lending and borrowing capital, almsgiving, and trade integrity. This activity shows that religion plays a role not only as a spiritual guide but also as a motivator and regulator in economic and social life. This study sheds light on how economic dynamics influence women’s religious and social lives in Minangkabau, emphasizing the necessity of understanding cultural and economic changes within a broader social context.